THE INFLUENCE OF FAMILY ENVIRONMENT AND ENTREPRENEURSHIP EDUCATION ON ENTREPRENEURIAL BEHAVIOR IN MSMES IN MEDAN KOTA DISTRICT - Ikhwan Alparisi; Nur Aisyah; Dahrul Siregar; Riza Fanny Meutya (Faculty of Economics dan Business, Atma Jaya Makassar University, 2023)
The purpose of this study is to analyze whether the entrepreneurial behavior of MSMEs (ministry of micro small & medium enterprises) in the Medan Kota District is influenced by the family environment and entrepreneurship education. This study applies descriptive research and a quantitative approach. Multiple linear regression with SPSS is used to measure results. The population of this study consists of 99 MSMEs in Medan Kota District. The questionnaire method is used for sampling. The t test and the coefficient of determination (R2) are used to check the hypotheses. Data analysis techniques using instrument test, classical assumption test, statistical test, and hypothesis test. Based on the research findings, it is known that there are two things that are true, the family environment influences the entrepreneurial behavior of MSMEs in Medan City District; the more conducive the family environment is for MSMEs, the more likely MSMEs are to exhibit entrepreneurial behavior, and entrepreneurship education influences MSME entrepreneurial behavior in Medan Kota District; the more knowledge MSMEs acquire from entrepreneurship education, the more likely MSMEs are to do so.